Addition of cystatin C predicts cardiovascular death better than creatinine in intensive care. Issue 4 (1st April 2021) - Helmersson-Karlqvist, Johanna; Lipcsey, Miklos; Ärnlöv, Johan; Bell, Max; Ravn, Bo; Dardashti, Alain; Larsson, Anders
Abstract : Objective: Decreased kidney function increases cardiovascular risk and predicts poor survival. Estimated glomerular filtration rate (eGFR) by creatinine may theoretically be less accurate in the critically ill. This observational study compares long-term cardiovascular mortality risk by the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine equation; Caucasian, Asian, paediatric and adult cohort (CAPA) cystatin C equation and the CKD-EPI combined creatinine/cystatin C equation. Methods: The nationwide study includes 22 488 intensive care patients in Uppsala, Karolinska and Lund University Hospitals, Sweden, between 2004 and 2015. Creatinine and cystatin C were analysed with accredited methods at admission. Reclassification and model discrimination with C-statistics was used to compare creatinine and cystatin C for cardiovascular mortality prediction. Results: During 5 years of follow-up, 2960 (13 %) of the patients died of cardiovascular causes. Reduced eGFR was significantly associated with cardiovascular death by all eGFR equations in Cox regression models. In each creatinine-based GFR category, 17%, 19% and 31% reclassified to a lower GFR category by cystatin C. These patients had significantly higher cardiovascular mortality risk, adjusted HR (95% CI), 1.55 (1.38 to 1.74), 1.76 (1.53 to 2.03) and 1.44 (1.11 to 1.86), respectively, compared with patients not reclassified. Harrell's C-statistic for cardiovascular death for cystatin C, alone or combined with creatinine, was 0.73, significantly higher than for creatinine (0.71), p<0.001. Conclusions: A single cystatin C at admission to the intensive care unit added significant predictive value to creatinine for long-term cardiovascular death risk assessment. Cystatin C, alone or in combination with creatinine, should be used for estimating GFR for long-term risk prediction in critically ill.